2007
DOI: 10.1021/jm070109i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of (±)-Abyssinone II and Its Analogues as Aromatase Inhibitors for Chemoprevention of Breast Cancer

Abstract: An efficient and economical synthesis of the naturally occurring aromatase inhibitor abyssinone II was performed. The synthesis features an optimized aromatic prenylation reaction in which an arylcopper intermediate is reacted with prenyl bromide to afford a key intermediate that was converted to a prenylated aromatic aldehyde. Condensation of the aldehyde with an o-hydroxyacetophenone under Claisen-Schmidt conditions afforded a chalcone that was deprotected and cyclized in the presence of sodium acetate in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 31 publications
1
86
0
1
Order By: Relevance
“…6) showed that both absorptive permeability and the secretory permeability increased and the efflux ratio remained about the same in the presence of MRP inhibitor LTC 4 and BCRP inhibitor dipyridamole. However, in the presence of 20μM verapamil, the absorptive permeability significantly increased, whereas secretory permeability significantly decreased, which resulted in a 70% reduction in the efflux ratio (from 4.88 to 1.49).…”
Section: Inhibition Studymentioning
confidence: 96%
See 1 more Smart Citation
“…6) showed that both absorptive permeability and the secretory permeability increased and the efflux ratio remained about the same in the presence of MRP inhibitor LTC 4 and BCRP inhibitor dipyridamole. However, in the presence of 20μM verapamil, the absorptive permeability significantly increased, whereas secretory permeability significantly decreased, which resulted in a 70% reduction in the efflux ratio (from 4.88 to 1.49).…”
Section: Inhibition Studymentioning
confidence: 96%
“…1) are widely distributed in the plant world and have a variety of biological effects including anticancer and anti-aging (e.g., alleviating aging-related degenerative diseases) (1)(2)(3). Prenylated flavonoids also serve as lead compounds to the development of novel estrogen receptor agonists and antagonists (4). Several prenylated flavonoids (e.g., 8-prenylated-naringenin) are also widely consumed because they are present in hops that are used to make beer (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, only one compound showed inhibition potential and it was less potent than racemic abyssinone II. The successful derivative featured two hydroxyl groups on the A ring and one methoxy group accompanied by a 3-methylbutyl-2-enyl substituent on B ring [112].…”
Section: Effects Of Chalcones On Tumor Promotionmentioning
confidence: 99%
“…An in vitro recombinant expressed aromatase activity assay was conducted as described previously with minor modifications (Stresser et al, 2000;Maiti et al, 2007). In brief, the test compounds (5 ml) were preincubated with an NADPH regenerating system (45 ml of 2.6 mM NADP þ , 7.6 mM glucose-6-phosphate, 0.8 U/ml glucose-6-phosphate dehydrogenase, and 1 mg/ml albumin, in 50 mM potassium phosphate, pH 7.4) for 10 min at 37 1C before 50 ml of the enzyme and substrate mixture (40 pM recombinant aromatase and 0.4 mM dibenzylfluorescein in 50 mM potassium phosphate, pH 7.4) were added.…”
Section: Recombinant Expressed Aromatase Activity Assaymentioning
confidence: 99%